Multimodel estimates of atmospheric lifetimes of long‐lived ozone‐depleting substances: Present and future. Issue 5 (1st March 2014) - Chipperfield, M. P.; Liang, Q.; Strahan, S. E.; Morgenstern, O.; Dhomse, S. S.; Abraham, N. L.; Archibald, A. T.; Bekki, S.; Braesicke, P.; Di Genova, G.; Fleming, E. L.; Hardiman, S. C.; et al.
Abstract We have diagnosed the lifetimes of long‐lived source gases emitted at the surface and removed in the stratosphere using six three‐dimensional chemistry‐climate models and a two‐dimensional model. The models all used the same standard photochemical data. We investigate the effect of different definitions of lifetimes, including running the models with both mixing ratio (MBC) and flux (FBC) boundary conditions. Within the same model, the lifetimes diagnosed by different methods agree very well. Using FBCs versus MBCs leads to a different tracer burden as the implied lifetime contained in the MBC value does not necessarily match a model's own calculated lifetime. In general, there are much larger differences in the lifetimes calculated by different models, the main causes of which are variations in the modeled rates of ascent and horizontal mixing in the tropical midlower stratosphere. The model runs have been used to compute instantaneous and steady state lifetimes. For chlorofluorocarbons (CFCs) their atmospheric distribution was far from steady state in their growth phase through to the 1980s, and the diagnosed instantaneous lifetime is accordingly much longer. Following the cessation of emissions, the resulting decay of CFCs is much closer to steady state. For 2100 conditions the model circulation speeds generally increase, but a thicker ozone layer due to recovery and climate change reduces photolysis rates. These effects compensate so the net impact on modeled lifetimes is small. For future assessments of stratospheric ozone, use of FBCs would allow a consistent balance between rate of CFC removal and model circulation rate.